End of life care for older cancer patients in China: lived experiences from patients, family caregivers and health professionals - Cui, Bing (2021)
This thesis examines the lived experiences of end of life care for older cancer patients in China, as perceived by patients, family caregivers and health professionals. Data were generated from unstructured, in-depth, face to face interviews with 37 participants, including ten patients aged 60 and above with advanced cancer, twelve family caregivers who looked after older cancer patients, and eight doctors and seven nurses, from three healthcare settings, i.e. the oncology department of a hospital, a hospice centre and a community clinic. Three main themes were found from the data analysis, including diagnosis disclosure, living with cancer, and attitudes towards treatment. In each theme, several subthemes were identified for each group of participants as the main components of their experiences. Diagnosis disclosure in China followed a family-oriented paradigm so that patients had different ways of knowing and various levels of awareness of their illness. Chinese cultural and social background, as well as the ethical precedence of beneficence for the patients, contribute to the phenomenon of family-oriented disclosure practice. Cancer patients experienced psychological distress and existential challenges when living with cancer. They adopted different coping strategies with the confrontation strategy as the main approach. Family caregivers’ stress was prominent, but their well-being was usually overlooked. Cancer patients and their families had a fighting spirit toward cancer and were actively involved in curative treatment due to unrealistic hope. Their attitudes would also lead to resistance to palliative care. The findings from this study contribute to the limited literature on relevant end of life care issues in China and have important implications for service users, health professionals and policymakers at local and national levels.